Microfiber insulation products

JP2024522502A5Active Publication Date: 2025-04-08OWENS CORNING INTELLECTUAL CAPITAL LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023572974
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-06-04
Filing Date
2022-06-03
Publication Date
2025-04-08
Estimated Expiration
2042-06-03

AI Technical Summary

Technical Problem

Existing fiberglass insulation products face challenges in achieving improved thermal performance and material efficiency while maintaining a reduced fiber diameter below 4 microns, as this reduction typically compromises insulation value and increases product weight.

Method used

The development of fiberglass insulation products with glass fibers having an average diameter ranging from 8 to 15 microns, oriented within specific angular ranges, and coated with a formaldehyde-free binder composition to enhance fiber alignment and reduce binder gussets, resulting in improved thermal conductivity and material efficiency.

Benefits of technology

The solution achieves significantly lower thermal conductivity and higher material efficiency, allowing for effective insulation performance with reduced weight and thickness, surpassing expected results in thermal insulation values.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

An insulation product is disclosed having a plurality of glass fibers and a crosslinked formaldehyde-free binder composition at least partially coating the glass fibers. The glass fibers have an average fiber diameter in the range of 8HT (2.03 μm) to 15HT (3.81 μm). The insulation product is structured such that at least 30% by weight of the glass fibers in the insulation product are oriented within ±15° of a common plane defined by the length and width of the insulation product. The insulation product has a density of 0.2 pcf to 1.6 pcf when uncompressed.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THE DISCLOSURE This application relates generally to fiberglass insulation products, and more particularly to fiberglass insulation products having improved performance characteristics.

[0002] [Citation to Related Applications] This application claims priority to and any benefit of U.S. Provisional Patent Application No. 63 / 196,882, filed June 4, 2021, which is incorporated by reference in its entirety. [Background technology]

[0003] The term "fibrous insulation products" includes various compositions, various articles of manufacture, and various manufacturing processes. Mineral fibers, such as glass fibers, are commonly used in insulation products and nonwoven mats. Fiber insulation is typically produced by fiberizing a molten composition of polymer, glass, or other minerals and spinning the fibers from a fiberizer, such as a rotating spinner. To form the insulation product, the fibers produced by the rotating spinner are pulled downward from the spinner by a blower toward a conveyor. As the fibers move downward, a binder material is blown onto the fibers, and the fibers are collected on the conveyor in a high-loft continuous blanket. The fiber-binder matrix provides the insulation product with resilience for recovery after packaging, as well as stiffness and handleability, so that the insulation product can be handled and applied as needed within the insulation cavity of a building. The binder composition also provides protection to the fibers from interfilament abrasion and promotes compatibility between the individual fibers.

[0004] The blanket containing the binder-coated fibers is then passed through a curing oven and the binder is cured to set the blanket to a desired thickness. After the binder composition has cured, the fibrous insulation can be cut to length to form individual insulation products, and the insulation products can be packaged for shipping to a customer location. One typical insulation product manufactured is an insulation batt or blanket, which is suitable for use as cavity or airspace (e.g., wall, floor, ceiling) insulation in a residence or other building, and may be used to insulate an attic or other portion within a building. Such insulation batts or blankets are typically one-piece structures that are relatively flexible or rollable. Another common insulation product is air-blown or loose-pack insulation, which is suitable for use as sidewall and attic insulation in residential and commercial buildings as well as some hard-to-reach locations. Such loose pack insulation is often formed as many relatively small separate pieces, tufts, or the like, which may or may not have a binder applied thereto. Bulk insulation may also be formed in small cubes that are cut from the insulation blanket, compressed, and packaged in bags.

[0005] The insulating performance of an insulating material is determined primarily by the ratio of the thickness of the material divided by its thermal conductivity (k), which is the amount of heat that must be transferred through one square foot (0.0929 m) of insulation to raise or lower the temperature by one degree from one side of the insulation to the other. 2 ) of a material. The greater the thickness and the lower the k value, the better the insulating performance of the material.

[0006] Fiber insulation building products require low thermal conductivity to be effective insulators within wall and ceiling cavities. It is also desirable to reduce the overall product weight, and reducing product weight generally has a negative impact on thermal performance. In particular, attempts have been made to reduce product weight by reducing the diameter of the fibers used to form the fiber insulation products, but such fiber insulation products have traditionally had an average fiber diameter of about 4 microns (one micron is equal to 3.94 thousandths of an inch, or 3.94HT), or greater. Summary of the Invention [Problem to be solved by the invention]

[0007] However, such reductions in fiber diameter have previously been found to negatively impact the insulation value (R-value) of a product for a particular areal weight and product thickness. Thus, it has previously been impractical to reduce the average fiber diameter of an insulation product below 4 microns because such products have been unable to meet performance requirements while still being economical. Thus, there is a heretofore unmet need for insulation products made with fibers finer than 4 microns that can effectively meet necessary performance requirements, such as thermal performance, yet still improve overall material efficiency. [Means for solving the problem]

[0008] Various aspects of the inventive concept relate to an insulation product having a plurality of glass fibers and a crosslinked formaldehyde-free binder composition at least partially coating the glass fibers, the insulation product having a length, a width, and a thickness, the length being greater than each of the width and the thickness. The glass fibers have an average fiber diameter in the range of 8HT (2.03 μm) to 15HT (3.81 μm). The insulation product is structured such that at least 30% by weight of the glass fibers in the insulation product are oriented within ±15° of a common plane defined by the length and width of the insulation product. In some exemplary embodiments, at least 40% by weight of the glass fibers are oriented within ±15° of the common plane. For any of the exemplary embodiments disclosed herein, the common plane may be parallel to the length and width directions of the insulation product. The insulation product has a density of 0.2 pcf to 1.6 pcf when uncompressed.

[0009] For any of the exemplary embodiments disclosed herein, at least 15% by weight of the glass fibers in the insulation product may be at least partially bundled in a substantially parallel orientation with at least one other glass fiber in the insulation product.

[0010] For any of the exemplary embodiments disclosed herein, the formaldehyde-free binder composition may include at least one monomeric polyol and at least one polycarboxylic acid in a total amount of at least 45% by weight, based on the total weight of the binder composition, prior to crosslinking. In these and other embodiments, the formaldehyde-free binder composition is free of Maillard reactants.

[0011] In some exemplary embodiments, the glass fibers are oriented such that no more than 35% by weight of the binder composition is present in the form of gussets.

[0012] Another exemplary embodiment relates to an insulation product comprising a plurality of glass fibers having an average fiber diameter in the range of 8HT (2.03 μm) to 15HT (3.81 μm) and a crosslinked formaldehyde-free binder composition at least partially coating the glass fibers, where prior to crosslinking, the binder composition has a viscosity of less than 40,000 cP at a solids content of 65% to 70% by weight, and the binder composition includes at least one monomeric polyol. The insulation product has a length, a width, and a thickness, and the length is greater than each of the width and the thickness. The insulation product is structured such that at least 55% by weight of the glass fibers are oriented within ±30° of a common plane defined by the length and width of the insulation product, and at least 15% by weight of the glass fibers in the insulation product are at least partially bundled in a substantially parallel orientation with at least one other glass fiber in the insulation product. The insulation product may have a density of 0.2 pcf to 1.6 pcf when uncompressed.

[0013] For any of the exemplary embodiments disclosed herein, the glass fibers are oriented such that no more than 35% by weight of the binder composition is present in the form of gussets.

[0014] For any of the exemplary embodiments disclosed herein, at least 80% by weight of the glass fibers are oriented within ±50° of a common plane.

[0015] For any of the exemplary embodiments disclosed herein, the common plane may be parallel to the length of the insulation product.

[0016] Yet another embodiment relates to an insulation product comprising a plurality of glass fibers having an average fiber diameter less than 15HT and a crosslinked formaldehyde-free binder composition at least partially coating the glass fibers, the crosslinked formaldehyde-free binder composition being formed from an aqueous binder composition comprising at least one monomeric polyol. The insulation product is structured such that at least 15% by weight of the glass fibers in the insulation product are at least partially bundled in a substantially parallel orientation with at least one other glass fiber in the insulation product. Additionally, the glass fibers may be oriented such that no more than 35% by weight of the binder composition is present in the form of gussets.

[0017] In these and other embodiments, the insulation product is structured such that at least 30%, and in some cases at least 40%, by weight of the glass fibers are oriented within ±15° of a common plane defined by the width and length of the insulation product. In certain exemplary embodiments, the common plane is parallel to the length and width of the insulation product.

[0018] For any of the exemplary embodiments disclosed herein, the glass fibers may have an average fiber diameter of between 12HT and 14.5HT.

[0019] Yet another exemplary embodiment relates to a method of forming an insulation product, the method including fiberizing molten glass into a plurality of glass fibers, coating the glass fibers with an aqueous formaldehyde-free binder composition, randomly depositing the glass fibers on a moving conveyor to form an uncured fiberglass blanket, and passing the uncured fiberglass blanket through a curing oven to crosslink the binder composition to form a fibrous insulation product, the insulation product having a length, a width, and a thickness, the length being greater than each of the width and the thickness.

[0020] Upon introduction into the curing oven, the uncured fiberglass blanket should have a reduced moisture content, such as a moisture content of 3% or less, or 2% or less, by weight.

[0021] For any of the exemplary embodiments disclosed herein, the insulation product may be structured such that at least 30% by weight of the glass fibers are oriented within ±15° of a common plane of the insulation product. Additionally, the insulation product has a density of 0.2 pcf to 1.6 pcf when uncompressed.

[0022] Various features and advantages of the present invention will become apparent to those skilled in the art to which the present invention pertains from the following description taken in conjunction with the accompanying drawings. [Brief description of the drawings]

[0023] [Figure 1] 1 is a perspective view of an exemplary embodiment of a fibrous insulation product. [Diagram 2] 2 is an elevational view of an exemplary embodiment of a manufacturing line for producing the fibrous insulation product of FIG. 1. [Diagram 3] FIG. 2 is a scanning electron microscope ("SEM") image showing a cross-section of an exemplary fibrous insulation product formed from glass fibers having an average fiber diameter of 14.5HT. [Figure 4] FIG. 2 is a SEM image showing a cross-section of an exemplary fibrous insulation product formed from glass fibers having an average fiber diameter of 14.5HT. [Diagram 5] FIG. 2 is a SEM image of a cross-section of a conventional fiber insulation product made of glass fibers with an average fiber diameter of 16.7 HT and an insulation value of R-21. [Figure 6] FIG. 1 is a graphical illustration of fiber orientation distribution within ±15° from a plane parallel to the product length L1 (0°) taken at a cross section along the machine direction of an exemplary fibrous insulation product formed with glass fibers having an average fiber diameter of 14.5HT. [Figure 7] FIG. 1 is a graphical illustration of fiber orientation distribution within ±30° from a plane parallel to the product length L1 (0°) taken at a cross section along the machine direction of an exemplary fibrous insulation product formed of glass fibers having an average fiber diameter of 14.5HT. [Figure 8]FIG. 1 is a graphical illustration of fiber orientation distribution within ±50° from a plane parallel to the product length L1 (0°) taken at a cross section along the machine direction of an exemplary fibrous insulation product formed of glass fibers having an average fiber diameter of 14.5HT. [Figure 9(a)] FIG. 2 is a SEM image showing fiber orientation of a 24 mm×16 mm cross section of an exemplary microfiber insulation product formed from glass fibers having an average fiber diameter of about 14HT. [Figure 9(b)] FIG. 9(b) is a graphical illustration of a fiber orientation distribution curve (measured in degrees, based on a plane parallel to the product length L1 (0°)) taken at a cross section along the machine direction of the fibrous insulation product of FIG. 9(a). [Figure 10(a)] FIG. 2 is a SEM image showing fiber orientation of a 24 mm×16 mm cross section of an exemplary microfiber insulation product formed from glass fibers having an average fiber diameter of about 14HT. [Figure 10(b)] FIG. 10(b) is a graphical illustration of a fiber orientation distribution curve (measured in degrees, based on a plane parallel to the product length L1 (0°)) taken at a cross section along the machine direction of the fibrous insulation product of FIG. 10(a). [Figure 11(a)-11(c)] 11(a)-11(c) are SEM images showing the parallel fiber bundles present in an exemplary fibrous insulation product formed from glass fibers having an average fiber diameter of 14.5HT. [Figure 12(a)-12(c)] 12(a)-12(c) are SEM images showing the parallel fiber bundles present in an exemplary fibrous insulation product formed from glass fibers having an average fiber diameter of 14.5HT. [Figure 13(a)-13(b)] 13(a) and 13(b) are SEM images showing binder gussets present in an exemplary fibrous insulation product formed from glass fibers having an average fiber diameter of 14.5HT. [Figure 14] FIG. 1 is a graphical illustration of a predicted thermal conductivity (k value) curve per product density compared to an actual thermal conductivity (k value) curve per product density. [Figure 15] FIG. 1 is a graphical illustration of a predicted material efficiency curve per product density compared to an actual material efficiency curve per product density. [Figure 16]FIG. 1 is a graphical illustration of a predicted material efficiency curve per product density compared to an adjusted material efficiency curve per product density. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention pertains. The terms used in the description of this specification are only for describing the exemplary embodiments and are not meant to limit the exemplary embodiments. Therefore, the technical concept of the general invention is not limited to the specific embodiments described herein. Although other methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present invention, the preferred methods and materials are described herein.

[0025] As used in the specification and claims, the singular forms "a," "an," and "the" are intended to include the plural forms unless the context clearly dictates otherwise.

[0026] Unless otherwise specified, all numerical values ​​expressing size ranges, such as amounts of ingredients, properties such as molecular weight, properties such as molecular weight, reaction conditions, and physical and measured attributes, and other numerical values ​​used in the specification and claims should be understood in all instances as being modified by the term "about." Accordingly, unless specified to the contrary, the numerical properties set forth in the specification and claims are approximations that may vary depending upon the desired properties to be obtained in the embodiments herein. At the very least, each numerical parameter should be construed in light of significant digits and ordinary rounding approaches.

[0027] Unless otherwise specified, any element, any property, any feature, or combination of elements, properties, and features can be used in any embodiment disclosed herein, regardless of whether the element, property, feature, or combination of elements, properties, and features is explicitly disclosed in the embodiment. As will be readily understood, features described in connection with any particular aspect described herein can be used with other features described herein, provided such features are compatible with the aspect. In particular, features described in connection with the method can be used with a textile product or vice versa, features described in connection with the method can be used with an aqueous binder composition or vice versa, and features described in connection with the textile product can be used with an aqueous binder composition or vice versa.

[0028] Notwithstanding that the numerical ranges and parameters setting forth the illustrative embodiments are approximations, the numerical values ​​set forth in the specific examples are reported as precisely as possible. Any numerical value, however, inherently contains certain errors necessarily resulting from the standard deviation found in their respective testing measurements. Every numerical range given throughout this specification and claims will include every narrower numerical range that falls within such broader numerical range, as if all such narrower numerical ranges were expressly written herein.

[0029] As used herein, the terms "binder composition," "aqueous binder composition," "binder formulation," "binder," and "binder system" may be used interchangeably and are synonymous. Additionally, as used herein, the terms "formaldehyde-free" or "no added formaldehyde" may be used interchangeably and are synonymous.

[0030] All ranges are understood to include all possible subranges within the outer boundaries of that range. Thus, for example, a density range of 0.2 pcf to 2.0 pcf discloses, for example, 0.5 pcf to 1.2 pcf, 0.7 pcf to 1.0 pcf, etc.

[0031] The term "substantially free" means that the composition contains less than 1.0% by weight of the recited component, including amounts of 0.8% or less, 0.6% or less, 0.4% or less, 0.2% or less, 0.1% or less, 0.5% or less, and 0.01% or less by weight.

[0032] As used herein, the unit "pound" or "lb" refers to pounds-mass (1 pound = 453.6 g).

[0033] The present disclosure relates to fiberglass insulation products formed with small diameter glass fibers (i.e., fibers having an average fiber diameter of 15HT or less) to achieve preferred fiber orientation and product structure. The fiberglass insulation products have surprisingly demonstrated improved thermal performance and overall material efficiency.

[0034] The fibrous insulation products of the present invention are comprised of a plurality of fibers, such as organic or inorganic fibers, hi certain exemplary embodiments, the plurality of fibers are inorganic fibers, including, but not limited to, glass fibers, glass wool fibers, mineral wool fibers, slag wool fibers, stone wool fibers, ceramic fibers, metal fibers, and combinations thereof.

[0035] Optionally, the fibers may include natural and / or synthetic fibers, such as carbon, polyester, polyethylene, polyethylene terephthalate, polypropylene, polyamide, aramid, and / or polyaramid fibers. As used herein, the term "natural fibers" refers to plant fibers extracted from any part of a plant, including, but not limited to, stems, seeds, leaves, roots, or phloem. Examples of natural fibers suitable for use as insulation products include wood fibers, cellulose fibers, straw, wood chips, wood strands, cotton, jute, bamboo, ramie, bagasse, hemp, coir, linen, kenaf, sisal, flax, henequen, and combinations thereof. The fiber insulation product may be made entirely of one type of fiber, or may be formed of a combination of various fibers. For example, the fiber insulation product may be formed of a combination of various glass fibers or various combinations of various inorganic and / or natural fibers depending on the desired application for insulation. For any of the embodiments disclosed herein, the insulation product may be substantially or entirely made of glass fibers.

[0036] Fiber insulation products utilize glass fibers having smaller diameters than those used in conventional fiberglass insulation products, particularly residential insulation products, which typically have fiber diameters greater than 4 μm (15.7 HT). Specifically, exemplary fiber insulation products disclosed or suggested herein may have glass fibers with an average fiber diameter of 3.81 μm (15 HT) or less prior to application of the binder composition, including average fiber diameters of 3.76 μm (14.8 HT) or less, 3.68 μm (14.5 HT) or less, 3.61 μm (14.2 HT) or less, 3.56 μm (14 HT) or less, 3.43 μm (13.5 HT) or less, 3.30 μm (13 HT) or less, 3.18 μm (12.5 HT) or less, and 3.05 μm (12 HT) or less. For any of the exemplary embodiments, the fibrous insulation product may include glass fibers having an average fiber diameter in the range of 3.05 μm (12.0HT) to 3.81 μm (15.0HT), 3.30 μm (13.0HT) to 3.76 μm (14.8HT), or 3.43 μm (13.5HT) to 3.61 μm (14.2HT). In other exemplary embodiments, the insulation product may include glass fibers having an average fiber diameter in the range of 2.03 μm (8.0HT) to 3.05 μm (12.0HT), 2.29 μm (9.0HT) to 2.79 μm (11.0HT), or 2.03 μm (8.0HT) to 2.54 μm (10.0HT).

[0037] An exemplary procedure used to measure the diameter of glass fibers utilizes a scanning electron microscope (SEM) to directly measure fiber diameter. Typically, a test piece of a fiber insulation product is heated to remove any organic material (e.g., binder composition) from the test piece, and then the length of the glass fiber from the test piece is reduced and photographed by the SEM. The diameter of the fiber is then measured from the image stored by image processing software associated with the SEM.

[0038] Specifically, a test specimen of the fibrous insulation product is heated to 800°F (426.7°C, where °F = (°F-32) x (5 / 9)) for a minimum of 30 minutes. The specimen may be heated longer if necessary to ensure removal of any organic material. The specimen is then cooled to room temperature and the glass fibers are reduced in length so that they can be fitted onto an SEM planchette. The glass fibers can be reduced in length by any suitable method, such as by cutting with scissors, cutting with a razor blade, or grinding with a mortar and pestle. The glass fibers are then attached to the surface of the SEM planchette so that the fibers do not overlap or are spaced too far apart.

[0039] Once the specimen is prepared for imaging, it is mounted in the SEM using normal operating procedures and photographed by the SEM at a magnification appropriate to the diameter size of the fiber to be measured. A sufficient number of images are collected and stored so that a sufficient amount of fibers are available for measurement. For example, 10-13 images may be required, in which case 250-300 fibers are measured. The fiber diameters are then measured using an SEM image analysis software program, such as Scandium SIS Imaging Software. The average fiber diameter of the specimen is then calculated from the number of fibers measured. The fiber insulation product specimen may include glass fibers that are fused together (i.e., two or more fibers are joined along their length). For purposes of calculating the average fiber diameter of the specimen in this disclosure, the fused fibers are treated as a single fiber.

[0040] Another procedure used to measure the average fiber diameter of glass fibers utilizes an apparatus that measures air flow resistance to indirectly determine the average or "effective" fiber diameter of randomly distributed fibers in the test specimen. Specifically, in one embodiment of the alternative procedure, a test specimen of a fiber insulation product is heated to 800-1000°F (426.7-537.8°C) for 30 minutes. The test specimen is heated longer if necessary to remove any organic material. The test specimen is then cooled to room temperature, and a test specimen weighing approximately 7.50 grams is placed in the chamber of the apparatus. A constant air flow is introduced into the chamber, and once the air flow has stabilized, the differential pressure or pressure drop is measured by the apparatus. Based on the air flow rate and the differential pressure, the apparatus can compute the average fiber diameter of the test specimen.

[0041] The fibrous insulation product of the present invention comprises a "formaldehyde-free" or "formaldehyde-free" aqueous binder composition used to bind inorganic fibers in the manufacture of the insulation product. "Binder composition" refers to an organic agent or chemical, often a polymeric resin, used to bind inorganic fibers together in a three-dimensional structure. The binder composition may be in any form, such as a solution, emulsion, or dispersion. Thus, "binder dispersion" or "binder emulsion" refers to a mixture of binder chemicals in a medium or vehicle. As used herein, "binder composition," "aqueous binder composition," "binder formulation," "binder," and "binder system" may be used interchangeably and are synonymous. Additionally, as used herein, the terms "formaldehyde-free" or "formaldehyde-free" may be used interchangeably and refer to a binder composition that contains less than about 1 ppm of formaldehyde when cured or otherwise dried. 1 ppm is based on the weight of the product being measured for formaldehyde emissions.

[0042] A wide variety of binder compositions can be used with the glass fibers of the present invention. For example, binder compositions are divided into two broad, mutually exclusive classes: thermoplastic and thermosetting. Both thermoplastic and thermosetting binder compositions can be used with the present invention. Thermoplastic materials can be repeatedly heated to a softened or molten state, and such thermoplastic materials revert to their previous state upon cooling. In other words, heating can cause a reversible change in the physical state of the thermoplastic material (e.g., from solid to liquid), but the thermoplastic material does not undergo any irreversible chemical reaction. Exemplary thermoplastic polymers suitable for use in the fiber insulation product 100 include, but are not limited to, polyvinyls (e.g., polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, and the like), polyethylene terephthalate (PET), polypropylene or polyphenylene sulfide (PPS), nylon, polycarbonate, polystyrene, polyamide, polyolefin, acrylic and methacrylic acid ester resins, and certain copolymers of polyacrylates.

[0043] In contrast, the term thermoset polymer refers to a range of systems that initially exist as liquids, but which, upon heating, undergo a reaction to form a solid, highly crosslinked matrix. Thus, thermoset compounds contain a reaction system, often a pair of reactants, that irreversibly crosslinks upon heating. Upon cooling, thermoset compounds do not revert to their previous liquid state, but remain in an irreversibly crosslinked state.

[0044] Reactants useful as thermosetting compounds generally contain one or more of several reactive functional groups, such as amine, amide, carboxyl, or hydroxyl groups. As used herein, "thermosetting compound" (and its derivatives, such as "thermosetting compound," "thermosetting binder," or "thermosetting binder") means at least one of such reactants, although it will be appreciated that more than one may be required to form the crosslinking system characteristic of thermosetting compounds. In addition to the primary reactant in a thermosetting compound, catalysts, processing aids, and other additives may be present.

[0045] One category of thermosetting binders includes various phenol-aldehyde, urea-aldehyde, melamine-aldehyde, and other condensation polymerization materials. Phenolic / formaldehyde binder compositions are a known thermosetting binder system and have historically been favored because they are inexpensive and can transition from a low viscosity liquid in the uncured state to a hard thermosetting polymer upon curing.

[0046] The formaldehyde-free thermosetting binder system may include a binder system based on polycarboxy polymer and polyol. One example is the polyacrylic acid / polyol / polyacid binder system described in U.S. Patent Nos. 6,884,849 and 6,699,945 to Chen et al., each of which is incorporated herein by reference in its entirety. Another example is the polycarboxy polymer / long-chain polyol / short-chain polyol binder system described in U.S. Patent Application Publication No. 2019 / 0106564 to Zhang et al., which is incorporated herein by reference in its entirety. Another example is the polycarboxy polymer / monomer polyol binder system described in U.S. Provisional Patent Application No. 63 / 086,267, which is incorporated herein by reference in its entirety. Yet another example is the polycarboxylic acid / polyol / nitrogen based protectant binder system described in U.S. Provisional Patent Application No. 63 / 073,013, the disclosure of which is incorporated herein by reference in its entirety.

[0047] A second category of formaldehyde-free thermosetting binder compositions is called "bio" or "natural" binders. "Bio-binders" and "natural binders" are used interchangeably herein to refer to binder compositions made with nutrient compounds, such as carbohydrates, proteins, or fats, that have multiple reactive functions. Because these binders are made with nutrient compounds, they are environmentally friendly. Bio-binder compositions are described in detail in U.S. Patent Application Publication No. 2011 / 0086567, filed Oct. 8, 2010, to Hawkins et al., which is incorporated herein by reference in its entirety.

[0048] In some exemplary embodiments, the binder comprises an Owens Corning Eco-Touch™ binder or an EcoPure™ binder, an Owens Corning Sustaina™ binder, or an Knauf ECOSE® binder.

[0049] Another reactant useful as a thermosetting compound is the triammonium citrate-D-glucose system, which is derived from the mixture of D-glucose monohydrate, anhydrous citric acid, water and aqueous ammonia. Additionally, carbohydrate reactants and polyamine reactants are useful thermosetting compounds, which are described in detail in U.S. Patent Nos. 8,114,210, 9,505,883 and 9,926,464, which are incorporated by reference in their entireties.

[0050] It has been surprisingly found that fibrous insulation products made with glass fibers having an average fiber diameter of less than 15HT have improved properties when made with a formaldehyde-free binder composition comprising a polyol and a primary crosslinking agent, such as a polycarboxylic acid or salt thereof. Particularly noteworthy improvements have been found when the polyol contained in the binder composition is a monomeric polyol.

[0051] The primary crosslinking agent may be any compound suitable for crosslinking polyols. Non-limiting examples of suitable crosslinking agents include polycarboxylic acid-based materials having one or more carboxyl groups (-COOH), such as polycarboxylic acid monomers and polycarboxylic acid polymers, including salts and anhydrides of these acids, and mixtures thereof. For any of the exemplary embodiments, the polycarboxylic acid may be a polymerized polycarboxylic acid, such as a homopolymer or copolymer of acrylic acid. Polymerized polycarboxylic acids may include polyacrylic acid (salts or anhydrides thereof) and polyacrylic acid-based resins, such as QR-1629S and Acumer 9932, both of which are commercially available from The Dow Chemical Company, polyacrylic acid compositions commercially available from CH Polymers, and polyacrylic acid compositions commercially available from Coatex. Acumer 9932 is a polyacrylic acid / sodium hypophosphite resin having a molecular weight of about 4000 and a sodium hypophosphite content of 6-7% by weight based on the total weight of the polyacrylic acid / sodium hypophosphite resin. QR-1629S is a polyacrylic acid / glycerin resin composition. Aquaset-529 is a composition comprising polyacrylic acid crosslinked with glycerol.

[0052] Polycarboxylic acids may include polymeric polycarboxylic acids, such as polyacrylic acid, poly(meth)acrylic acid, polymaleic acid, and similar polymeric polycarboxylic acids, anhydrides, salts, or mixtures of such acids, as well as acrylic acid, methacrylic acid, maleic acid, and similar carboxylic acids, anhydrides, salts, and mixtures of such acids.

[0053] For any of the exemplary embodiments, the polycarboxylic acid may include polycarboxylic acid monomers such as citric acid, itaconic acid, maleic acid, fumaric acid, succinic acid, adipic acid, glutaric acid, tartaric acid, trimellitic acid, hemimellitic acid, trimesic acid, tricarballylic acid, and the like, including salts, anhydrides, and mixtures thereof.

[0054] The crosslinking agent may in some cases be pre-neutralized with a neutralizing agent, such as organic and / or inorganic bases, such as sodium hydroxide, ammonium hydroxide, and diethylamine, and any type of primary, secondary, or tertiary amine (alkanolamine). In various exemplary embodiments, the neutralizing agent may include at least one of sodium hydroxide and triethanolamine.

[0055] The crosslinking agent is present in the binder composition in an amount of at least 30.0 wt%, based on the total solids content of the binder composition, including, but not limited to, at least 40 wt%, at least 45 wt%, at least 50 wt%, at least 52.0 wt%, at least 54.0 wt%, at least 56.0 wt%, at least 58.0 wt%, and at least 60.0 wt%. For any of the embodiments disclosed herein, the crosslinking agent is present in the aqueous binder composition in an amount of 30 wt% to 85 wt%, based on the total solids content of the aqueous binder composition, including, but not limited to, 50.0 wt% to 70.0 wt%, greater than 50 wt% to 65 wt%, and 52.0 wt% to 62.0 wt%, greater than 54.0 wt% to 60.0 wt%, and 55.0 wt% to 59.0 wt%.

[0056] Optionally, in addition to the polycarboxylic acid crosslinkers described above, the binder composition may alternatively include amine-based reactants, such as ammonium salts (e.g., ammonium salts of polycarboxylic acids), amines, diammonium sulfate, proteins, peptides, amino acids, etc. Such amine-based reactants can participate in Maillard reactions with reducing sugars to produce melanoidins (high molecular weight, furan ring and nitrogen-containing polymers). Thus, in some exemplary embodiments, the binder composition may include melanoidins produced by reaction of amine-based reactants with one or more reducing sugars.

[0057] The aqueous binder composition may further include at least one polyol. For any of the exemplary embodiments, the polyol may include a monomeric polyol. The monomeric polyol may include a water-soluble compound having a molecular weight of less than 2,000 Daltons (including less than 1,000 Daltons, less than 750 Daltons, less than 500 Daltons) and at least two hydroxyl (-OH) groups. Exemplary monomeric polyols include glucose, sucrose, ethylene glycol, sugar alcohols, pentaerythritol, primary alcohols, 2,2-bis(methylol)propionic acid, tri(methylol)propane (TMP), 1,2,4-butanetriol, trimethylolpropane, fructose, high fructose corn syrup (HFCS), and short chain alkanolamines containing at least three hydroxyl groups, such as triethanolamine. For any of the embodiments disclosed herein, the polyol may include at least three hydroxyl groups, at least four hydroxyl groups, or at least five hydroxyl groups.

[0058] Sugar alcohol is understood to mean the compound obtained when the aldo or keto group of a sugar is reduced (e.g., by hydrogenation) to the corresponding hydroxyl group. The starting sugar will be selected from among monosaccharides, oligosaccharides, and polysaccharides, as well as mixtures of these products, such as syrups, molasses, and starch hydrolysates. The starting sugar may also be a dehydrated form of a sugar. Although the sugar alcohol closely resembles the starting sugar, it is not a sugar, and in particular is not a reducing sugar. Thus, for example, sugar alcohols do not have reducing ability and cannot participate in the Maillard reaction characteristic of reducing agents. In some exemplary embodiments, the sugar alcohols include glycerol, erythritol, arabitol, xylitol, sorbitol, maltitol, mannitol, iditol, isomaltitol, lactitol, cellobitol, palatinitol, maltotritol, syrups thereof, and mixtures thereof. In various exemplary embodiments, the sugar alcohol is selected from glycerol, sorbitol, xylitol, and mixtures thereof. In some exemplary embodiments, the monomeric polyol is a dimeric or oligomeric condensation product of a sugar alcohol. In various exemplary embodiments, the condensation product of a sugar alcohol is isosorbide. In some exemplary embodiments, the sugar alcohol is a diol or a glycol.

[0059] In some exemplary embodiments, the monomeric polyol may be present in the aqueous binder composition in an amount of up to about 70% by weight of total solids, including, but not limited to, up to about 60%, up to about 55%, up to about 50%, up to about 40%, up to about 35%, up to about 33%, up to about 30%, up to about 27%, up to about 25%, and up to about 20% by weight of total solids. For some exemplary embodiments, the monomeric polyol may be present in the aqueous binder composition in an amount of 2.0% to 65.0% by weight of total solids, including, but not limited to, 5.0% to 40.0%, 8.0% to 37.0%, 10.0% to 34.0%, 12.0% to 32.0%, 15.0% to 30.0%, and 20.0% to 28.0% by weight of total solids.

[0060] In various exemplary embodiments, the crosslinker and monomeric polyol are present in amounts such that the ratio of the number of molar equivalents of carboxyl groups, anhydride groups, or salts thereof to the number of molar equivalents of hydroxyl groups is from about 0.3 / 1 to about 1 / 0.3, e.g., from about 0.5 / 1 to about 1 / 0.5, from about 0.6 / 1 to about 1 / 0.6, from about 0.8 / 1 to about 1 / 0.8, or from about 0.9 / 1 to about 1 / 0.9.

[0061] For any of the embodiments disclosed herein, the binder composition may be free or substantially free of polyols containing less than three hydroxyl groups, or free or substantially free of polyols containing less than four hydroxyl groups. For any of the embodiments disclosed herein, the binder composition may be free or substantially free of polyols having a number average molecular weight of 2,000 Daltons or more, such as a molecular weight of 3,000 Daltons to 4,000 Daltons. Thus, for any of the embodiments disclosed herein, the binder composition may be free or substantially free of diols, such as glycols, triols, such as glycerol and triethanolamine, and / or polymeric polyhydroxy compounds, which may be partially or fully hydrolyzed, such as polyvinyl alcohol, polyvinyl acetate, or mixtures thereof.

[0062] For any of the embodiments disclosed herein, the aqueous binder composition may comprise or consist of a crosslinker based on a polymeric polycarboxylic acid and a monomeric polyol with at least four hydroxyl groups, with a ratio of carboxylic acid groups to hydroxyl OH groups of 0.60 / 1 to 1 / 0.6.

[0063] However, in some exemplary embodiments, the polyol may comprise a polymeric polyol having at least two hydroxyl groups and a number average molecular weight of at least 2,000 Daltons. The polymeric polyol may be included as the only polyol in the binder composition, or the polymeric polyol may be included as a secondary polyol in addition to the monomeric polyols described above.

[0064] In some exemplary embodiments, the secondary polyol comprises one or more of a polymerized polyhydroxy compound, such as polyvinyl alcohol, polyvinyl acetate, which may be partially or fully hydrolyzed, or mixtures thereof. By way of example, when partially hydrolyzed polyvinyl acetate serves as the polyol component, 80% to 89% hydrolyzed polyvinyl acetate, such as Poval® 385 (Kuraray America, Inc.) and (Sekisui Specialty Chemicals America, LLC), which are about 85% (Poval® 385) and about 88% (Selvol™ 502), respectively, may be utilized. Another option is ELVANOL 51-05, or other partially hydrolyzed polyvinyl acetate, available from DuPont and having a molecular weight of about 22,000 to about 26,000 daltons and a viscosity of about 5.0 to 6.0 centipoise.

[0065] The secondary polyol may be present in the aqueous binder composition in an amount of up to about 30% by weight of total solids, including, but not limited to, up to about 28%, up to about 25%, up to about 20%, up to about 18%, up to about 15%, and up to about 13% by weight of total solids. For any of the exemplary embodiments, the secondary polyol may be present in the aqueous binder composition in an amount of 2.5% to 30% by weight of total solids, including, but not limited to, 5% to 25%, 8% to 20%, 9% to 18%, and 10% to 16% by weight of total solids.

[0066] In such an embodiment of the binder composition including a secondary polyol, the crosslinker, the monomeric polyol, and the secondary polyol have a ratio of the number of molar equivalents of carboxylic acid groups, anhydride groups, or salts thereof to the number of molar equivalents of hydroxyl groups of about 1 / 0.05 to about 1 / 5, such as about 1 / 0.08 to about 1 / 2.0, about 1 / 0.1 to about 1 / 1.5, and about 1 / 0.3 to about 1 / 0.66. Within this ratio range, the ratio of the secondary polyol to the monomeric polyol affects the performance of the binder composition, such as the tensile strength and water solubility of the binder after curing. For example, when the ratio of the secondary polyol to the monomeric polyol is about 0.1 / 0.9 to about 0.9 / 0.1, such as between about 0.3 / 0.7 to about 0.7 / 0.3, or about 0.4 / 0.6 to about 0.6 / 0.4, this provides a balance of desirable mechanical and physical color properties. In various exemplary embodiments, the ratio of secondary polyol to monomeric polyol is about 0.5 / 0.5.

[0067] For any of the aqueous binder compositions disclosed herein, all or a portion of the acid functionality of the polycarboxylic acid may be temporarily blocked by the use of a protective agent, which temporarily prevents the acid functionality from complexing with the mineral wool fibers, and which is subsequently removed during the curing process by heating the binder composition to a temperature of at least 150° C. to eliminate the acid functionality and crosslink with the polyol component and complete the esterification process. For any of the exemplary embodiments, 10% to 100% of the carboxylic acid functionality may be temporarily blocked with a protective agent, including about 25% to about 99%, about 30% to about 90%, about 40% to 85%, and all subranges and combinations of ranges therebetween. For any of the exemplary embodiments, a minimum of 40% of the acid functionality may be temporarily blocked with a protective agent.

[0068] The protective agent can reversibly bond to the carboxylic acid group of the crosslinker. For any of the exemplary embodiments, the protective agent includes any compound that includes a molecule that can form at least one reversible ionic bond with a single acid functional group. For any of the exemplary embodiments disclosed herein, the protective agent can include a nitrogen-based protective agent, such as an ammonia-based protective agent, an amine-based protective agent, or a mixture thereof. An exemplary ammonia-based protective agent includes ammonium hydroxide. An exemplary amine-based protective agent includes alkylamines and diamines, such as ethyleneimine, ethylenediamine, hexamethylenediamine, alkanolamines, such as ethanolamine, diethanolamine, triethanolamine, ethylenediamine-N,N'-disuccinic acid (EDDS), ethylenediaminetetraacetic acid (EDTA), and the like, or a mixture thereof. Additionally, alkanolamines can be used as both protective agents and participants in the crosslinking reaction to form esters in the cured binder. Thus, the alkanolamine has the dual function of a protecting agent and a polyol to crosslink with polycarboxylic acids via esterification.

[0069] Protecting agents function differently from conventional pH adjusters. Protecting agents as defined herein only temporarily and reversibly block acid functional groups in polymeric polycarboxylic acid components. In contrast, conventional pH adjusters, such as sodium hydroxide, permanently terminate the acid functional groups, thereby preventing crosslinking between the acid and carboxyl groups due to the blocked acid functional groups. Thus, the inclusion of traditional pH adjusters, such as sodium hydroxide, does not provide the desired effect of temporarily blocking the acid functional groups, while later freeing these functional groups during curing to allow crosslinking via esterification. Therefore, for any of the exemplary embodiments disclosed herein, the binder composition may be free or substantially free of conventional pH adjusters, such as sodium hydroxide and calcium hydroxide. Such conventional pH adjusters for high temperature applications do not permanently bond with carboxylic acid groups and free the carboxylic acid group functionality to allow crosslinking esterification.

[0070] Any of the binder compositions disclosed herein may further include an additive blend including one or more processing aids that improve the processability of the binder composition by reducing the viscosity and tack of the binder, resulting in a uniform insulating product with increased tensile strength and hydrophobicity. There are a variety of additives that can reduce the viscosity and / or tack of the binder composition, but traditional additives are hydrophilic in nature, and thus the inclusion of such additives increases the overall water absorption of the binder composition. The additive blend may include one or more processing aids. Examples of processing aids include surfactants, glycerol, 1,2,4-butanetriol, 1,4-butanediol, 1,2-propanediol, 1,3-propanediol, poly(ethylene glycol) (e.g., Carbowax™), monooleate polyethylene glycol (MOPEG), silicone, polydimethylsiloxane (PDMS) dispersions, mineral, paraffin, or vegetable oil emulsions and / or dispersions, waxes such as amide waxes (e.g., ethylene bis-stearamide (EBS)) and carbamoyl wax (e.g., ML-155), hydrophobized silica, ammonium phosphate, or combinations thereof. Surfactants include non-ionic surfactants, including non-ionic surfactants with alcohol functional groups. Exemplary surfactants include Surfynol®, alkyl polyglucosides (e.g., Glucopon®), and alcohol ethoxylates (e.g., Lutensol®).

[0071] The additive blend can include a single processing aid, a mixture of at least two processing aids, a mixture of at least three processing aids, or a mixture of at least four processing aids. For any of the embodiments disclosed herein, the additive blend can include a mixture of glycerol and polydimethylsiloxane.

[0072] The additive blend may be present in the binder composition in an amount of 1.0% to 20%, 1.25% to 17.0%, 1.5% to 15.0%, about 3.0% to 12.0%, or 5.0% to 10.0% by weight based on the total solids content in the binder composition. In any of the exemplary embodiments, the binder composition may include at least 7.0% by weight of the additive blend based on the total solids content in the binder composition, including at least 8.0% by weight and at least 9% by weight. Thus, in any of the exemplary embodiments, the aqueous binder composition may include 7.0% to 15% by weight of the additive blend based on the total solids content in the binder composition, including at least 8.0% by weight and at least 9% by weight.

[0073] In embodiments where the additive blend includes glycerol, the glycerol may be present in an amount of at least 5.0%, at least 6.0%, at least 7.0%, or at least 7.5% by weight based on the total solids in the binder composition. For any of the exemplary embodiments, the binder composition may include 5.0% to 15% by weight glycerol, including 6.5% to 13.0%, 7.0% to 12.0%, or 7.5% to 11.0% by weight based on the total solids in the binder composition.

[0074] In embodiments where the additive blend includes polydimethylsiloxane, the polydimethylsiloxane may be present in an amount of at least 0.2 wt%, at least 0.5 wt%, at least 0.8 wt%, or at least 1.0 wt%, at least 1.5 wt%, or at least 2.0 wt%, based on the total solids in the binder composition. For any of the exemplary embodiments, the binder composition may include from 0.5% to 5.0 wt% polydimethylsiloxane, based on the total solids in the binder composition, including from 1.0% to 4.0% by weight, from 1.2% to 3.5% by weight, from 1.5% to 3.0% by weight, and from 1.6% to 2.3% by weight.

[0075] For any of the embodiments disclosed herein, the additive blend may include a mixture of glycerol and polydimethylsiloxane, where the glycerol comprises 5.0-15% by weight of the binder composition and the polydimethylsiloxane comprises 0.5-5.0% by weight of the binder composition, based on the total solids content of the binder composition. For any of the embodiments disclosed herein, the additive blend may include a mixture of glycerol and polydimethylsiloxane, where the glycerol comprises 7.0-12% by weight of the binder composition and the polydimethylsiloxane comprises 1.2-3.5% by weight of the binder composition, based on the total solids content of the binder composition.

[0076] For any of the embodiments disclosed herein, the additive blend may include an increased concentration of a silane bonding agent. Conventional binder compositions generally include less than 0.5 wt. % silane, and more typically about 0.2 wt. % or less silane, based on the total solids content of the binder composition. Thus, for any of the embodiments disclosed herein, the silane bonding agent may be present in the binder composition in an amount of 0.5% to 5.0% by weight of the total solids in the binder composition, where 0.5% to 5.0% by weight includes about 0.7% to 2.5% by weight, 0.85% to 2.0% by weight, or 0.95% to 1.5% by weight. For any of the embodiments disclosed herein, the silane bonding agent may be present in the binder composition in an amount of up to 1.0% by weight.

[0077] Silane concentration may be further characterized by the amount of silane deposited on the fibers in the fiber insulation product. Typically, fiberglass insulation products contain 0.001% to 0.03% by weight of silane binder deposited on the glass fibers. However, by increasing the amount of silane binder contained on the fibers, the amount of silane deposited on the glass fibers is increased to at least 0.10% by weight.

[0078] Alternatively, the binder composition may include a conventional amount of a silane bonding agent, if present, in such an embodiment, the silane bonding agent may be present in the binder composition in an amount of from 0% to less than 0.5% by weight, by weight of the total solids in the binder composition, where from 0% to less than 0.5% by weight includes from 0.05% to 0.4% by weight, from 0.1% to 0.35% by weight, or from 0.15% to 0.3% by weight.

[0079] Non-limiting examples of silane bonding agents that can be used in the binder composition may be characterized by functional groups such as alkyl, allyl, amino, epoxy, vinyl, methacryloxy, ureido, isocyanato, and mercapto groups. In exemplary embodiments, the silane bonding agent includes silanes that contain one or more nitrogen atoms with one or more functional groups such as amine groups (primary, secondary, tertiary, and quaternary), amino groups, imino groups, amido groups, imido groups, ureido groups, or isocyanato groups. Specific non-limiting examples of suitable silane coupling agents include, but are not limited to, aminosilanes (e.g., triethoxyaminopropylsilane, 3-aminopropyl-triethoxysilane, and 3-aminopropyl-trihydroxysilane), epoxytrialkoxysilanes (e.g., 3-glycidoxypropyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane), methylacryltrialkoxysilanes (e.g., 3-methacryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane), hydrocarbontrialkoxysilanes, aminotrihydroxysilanes, epoxytrihydroxysilanes, methacryltrihydroxysilanes, and / or hydrocarbontrihydroxysilanes. In one or more exemplary embodiments, the silane is an aminosilane, such as gamma-aminopropyltriethoxysilane.

[0080] Any of the aqueous binder compositions disclosed herein may further include an esterification catalyst, also referred to as a cure accelerator. The catalyst may include inorganic salts, Lewis acids (i.e., aluminum chloride or boron trifluoride), Bronsted acids (i.e., sulfuric acid, p-toluenesulfonic acid, and boric acid), organometallic complexes (i.e., lithium carboxylate, sodium carboxylate), and / or Lewis bases (i.e., polyethyleneimine, diethylamine, or triethylamine). Additionally, the catalyst may include alkali metal salts of phosphorus-containing organic acids, particularly alkali metal salts of phosphoric acid, hypophosphorous acid, or polyphosphoric acid. Examples of such phosphorus catalysts include, but are not limited to, sodium hypophosphite, sodium phosphate, potassium phosphate, disodium pyrophosphate, tetrasodium pyrophosphate, sodium tripolyphosphate, sodium hexametaphosphate, potassium phosphate, potassium tripolyphosphate, sodium trimetaphosphate, sodium tetrametaphosphate, and mixtures thereof. In addition, the catalyst or cure accelerator may be a fluoroborate compound, such as fluoroboric acid, sodium tetrafluoroborate, potassium tetrafluoroborate, calcium tetrafluoroborate, magnesium tetrafluoroborate, zinc tetrafluoroborate, ammonium tetrafluoroborate, and mixtures thereof. In addition, the catalyst may be a mixture of a phosphorus compound and a fluoroborate compound. Other sodium salts, such as sodium sulfate, sodium nitrate, sodium carbonate, may also or alternatively be used as catalysts.

[0081] The catalyst may be present in the aqueous binder composition in an amount of from about 0% to about 10% by weight of the total solids of the binder composition, including, but not limited to, from about 1% to about 5% by weight, from about 2% to about 4.5% by weight, from about 2.8% to about 4.0% by weight, or from about 3.0% to about 3.8% by weight.

[0082] Optionally, the aqueous binder composition can include at least one coupling agent. In at least one exemplary embodiment, the coupling agent is a silane coupling agent. The coupling agent can be present in the binder composition in an amount of from about 0.01% to about 5%, from about 0.01% to about 2.5%, from about 0.05% to about 1.5%, or from about 0.1% to about 1.0% by weight of the total solids of the binder composition.

[0083] Non-limiting examples of silane bonding agents that can be used in the binder composition may be characterized by functional groups such as alkyl, allyl, amino, epoxy, vinyl, methacryloxy, ureido, isocyanato, and mercapto groups. In exemplary embodiments, the silane bonding agent includes silanes that contain one or more nitrogen atoms with one or more functional groups such as amine groups (primary, secondary, tertiary, and quaternary), amino groups, imino groups, amido groups, imido groups, ureido groups, or isocyanato groups. Specific non-limiting examples of suitable silane coupling agents include, but are not limited to, aminosilanes (e.g., triethoxyaminopropylsilane, 3-aminopropyl-triethoxysilane, and 3-aminopropyl-trihydroxysilane), epoxytrialkoxysilanes (e.g., 3-glycidoxypropyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane), methylacryltrialkoxysilanes (e.g., 3-methacryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane), hydrocarbontrialkoxysilanes, aminotrihydroxysilanes, epoxytrihydroxysilanes, methacryltrihydroxysilanes, and / or hydrocarbontrihydroxysilanes. In one or more exemplary embodiments, the silane is an aminosilane, such as gamma-aminopropyltriethoxysilane.

[0084] The aqueous binder composition may further include a processing aid. The processing aid is not particularly limited to the present invention, so long as the processing aid functions to facilitate the process of fiber forming and orientation. The processing aid may be used to improve binder application distribution uniformity, reduce binder viscosity, increase ramp height after forming, improve vertical weight distribution uniformity, and / or promote binder dehydration in both forming and oven curing processes. The processing aid may be present in the binder composition in an amount of 0 to about 10. wt%, about 0.1 wt% to about 5.0 wt%, about 0.3 wt% to about 2.0 wt%, or about 0.5 wt% to 1.0 wt%, based on the total solids in the binder composition. In some exemplary embodiments, the aqueous binder composition is substantially or completely free of any processing aid.

[0085] Examples of processing aids include defoamers, such as emulsions and / or dispersions of mineral, paraffin, or vegetable oils, polydimethylsiloxane (PDMS) fluids, and dispersions of silica hydrophobized with polydimethylsiloxane or other materials. Other processing aids may include amide waxes, such as ethylene bis-stearamide (EBS), or particles made of hydrophobized silica. Another processing aid that may be utilized in the binder composition is a surfactant. One or more surfactants may be included in the binder composition to aid in binder atomization, wetting, and interfacial adhesion.

[0086] The surfactant is not particularly limited and includes various surfactants, such as ionic surfactants (e.g., sulfates, sulfonates, phosphates, and carboxylates), sulfates (e.g., alkyl sulfates, ammonium lauryl sulfate, sodium lauryl sulfate (SDS), alkyl ether sulfates, sodium laureth sulfate, and sodium myreth sulfate), amphoteric surfactants (e.g., alkyl betaines, such as lauryl betaine), sulfonates (e.g., sodium dioctyl sulfosuccinate, perfluorooctane sulfonate, perfluorobutane sulfonate, and alkyl benzene sulfonates), phosphates (e.g., alkyl aryl ether phosphates and alkyl ether phosphates), carboxylates (e.g., alkyl carboxylates, , fatty acid salts (soaps), sodium stearate, sodium lauroyl sarcosinate, carboxylate fluorosurfactants, perfluoronanoate and perfluorooctanoate), cations (e.g., alkylamine salts, such as laurylamine acetate), pH-dependent surfactants (primary, secondary or tertiary amines), permanently charged quaternary ammonium cations (e.g., alkyltrimethylammonium salts, cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, cetylpyridinium chloride and benzethonium chloride) and zwitterionic surfactants, quaternary ammonium salts (e.g., lauryltrimethylammonium chloride and alkylbenzyldimethylammonium chloride) and polyoxyethylene alkylamines.

[0087] Suitable nonionic surfactants that can be used with the binder composition include polyethers (e.g., condensates of ethylene oxide and propylene oxide, including linear and branched alkyl and alkaryl polyethylene glycols and polypropylene glycol ethers and thioethers), alkylphenoxypoly(ethyleneoxy)ethanols having an alkyl group containing from about 7 to about 18 carbon atoms and having from about 4 to about 240 ethyleneoxy units (e.g., heptylphenoxypoly(ethyleneoxy)ethanol and nonylphenoxypoly(ethyleneoxy)ethanol), polyoxyalkylene derivatives of hexitols, including sorbitan, sorbide, mannitan, and mannide, partial long chain fatty acid esters (e.g., sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan tristearate, sorbitan tert-butyl ester ... polyoxyalkylene derivatives of sorbitan oleate, sorbitan monooleate and sorbitan trioleate), condensations of ethylene oxide with a hydrophobic base where the base is formed by condensing propylene oxide with propylene glycol, sulfur-containing condensates (e.g., condensations prepared by condensing ethylene oxide with higher alkyl mercaptans such as nonyl, dodecyl, or tetradecyl mercaptan, or with alkylthiophenols, where the alkyl group contains from about 6 to about 15 carbon atoms), ethylene oxide derivatives of long chain carboxylic acids (e.g., lauric acid, myristic acid, palmitic acid, and oleic acid, e.g., tall oil fatty acid), ethylene oxide derivatives of long chain alcohols (e.g., octyl, decyl, lauryl, or cetyl alcohol), and ethylene oxide / propylene oxide copolymers.

[0088] In at least one exemplary embodiment, the surfactant is selected from the group consisting of Dynol 607, which is 2,5,8,11-tetramethyl-6-dodecyne-5,8-diol, SURFONYL® 420, SURFONYL® 440, and SURFONYL® 465, which are ethoxylated 2,4,7,9-tetramethyl-5-decyne-4,7-diol surfactants (commercially available from Evonik Corporation, Allentown, Pa.), Stanfax (sodium lauryl sulfate), Surfynol 465 (ethoxylated 2,4,7,9-tetramethyl-5-decyne-4,7-diol), Triton™ GR-PG70 (sodium 1,4-bis(2-ethylhexyl) sulfosuccinate), and Triton™ CF-10. (poly(oxy-1,2-ethanediyl), alpha-(phenylmethyl)-omega-(1,1,3,3-tetramethylbutyl)phenoxy).

[0089] Optionally, the aqueous binder composition may include a dust suppressant to reduce or eliminate the presence of inorganic and / or organic particles that may adversely affect the subsequent fabrication and installation of the insulating material. The dust suppressant may be any conventional mineral oil, mineral oil emulsion, natural or synthetic oil, bio-based oil, or lubricating oil, such as, but not limited to, silicones and silicone emulsions, polyethylene glycol, and any petroleum or non-petroleum based oil with a high flash point to minimize evaporation of the oil in the oven.

[0090] The aqueous binder composition may include up to about 15% by weight of the dust suppressant, such as up to about 14% by weight, or up to about 13% by weight. For any of the embodiments disclosed herein, the aqueous binder composition may include from 1.0% to 15% by weight of the dust suppressant, such as from about 3.0% to about 13.0% by weight, or from about 5.0% to about 12.8% by weight.

[0091] The aqueous binder composition may optionally include organic and / or inorganic acids and bases as pH adjusters in an amount sufficient to adjust the pH to a desired level. The pH can be adjusted depending on the intended application to promote compatibility of the materials of the binder composition or to work with various types of fibers. In some exemplary embodiments, the pH adjuster is adjusted to adjust the pH of the binder composition to an acidic pH. Examples of suitable acidic pH adjusters include inorganic acids such as, but not limited to, sulfuric acid, phosphoric acid, and boric acid, as well as organic acids such as, but not limited to, p-toluenesulfonic acid, mono- or polycarboxylic acids such as citric acid, acetic acid and their anhydrides, adipic acid, oxalic acid, and their corresponding salts. Inorganic salts may also be used, which may be acid precursors. The acid adjusts the pH and, in some cases, acts as a crosslinking agent, as described above. Organic and / or inorganic bases may be included to increase the pH of the binder composition. The base may be a volatile or non-volatile base. Exemplary volatile bases include, for example, ammonia and alkyl-substituted amines such as methylamine, ethylamine or 1-aminopropane, dimethylamine and ethylmethylamine. Exemplary non-volatile bases include, for example, sodium hydroxide, potassium hydroxide, sodium carbonate, and t-butylammonium hydroxide.

[0092] For any of the exemplary embodiments, in the uncured state, the binder composition may have an acidic pH, for example, a pH in the range of about 2.0 to about 5.0, including all values ​​and ranges therebetween. For any of the embodiments disclosed herein, the pH of the binder composition in the uncured state may be about 2.2-4.0, including ranges of about 2.5-3.8 and about 2.6-3.5. After curing, the pH of the binder composition may increase to a pH of at least 5.0, including levels of about 6.5-8.8, or about 6.8-8.2.

[0093] Alternatively, the binder composition may be adjusted to a more alkaline pH, such as a pH of from about 5 to about 10, from about 6 to about 9, or from about 7 to about 8, in the uncured state.

[0094] The binder further comprises water to dissolve or disperse the active solids for application to the reinforcing fibers. Water may be added in an amount sufficient to dilute the aqueous binder composition to a suitable viscosity for application to the reinforcing fibers and to achieve the desired solids content on the fibers. It has been found that the binder composition of the present invention may comprise lower solids content than traditional phenolic-urea formaldehyde or carbohydrate-based binder compositions. In particular, the binder composition may comprise 5% to 35% by weight binder solids, including 10% to 30%, 12% to 20%, and 15% to 19% by weight of binder solids. This level of solids indicates that the binder composition of the present invention may comprise more water than conventional binder compositions.

[0095] Table 1 below lists exemplary binder compositions containing the materials described above. The exemplary compositions listed in Table 1 can include optional additives or materials as described above. TIFF2024522502000002.tif98153

[0096] An exemplary fiber insulation product 100 is shown in FIG. 1. The fiber insulation product 100 can be configured in a variety of ways. In the exemplary embodiment of FIG. 1, the fiber insulation product 100 is a generally box-shaped fiberglass insulation batt, but the insulation product can be of any suitable shape or size, such as a rolled product or blanket. As an insulation batt or blanket, the fiber insulation product 100 can be placed within an insulation cavity of a building. For example, the fiber insulation product 100 can be placed within the space or cavity between two parallel, spaced apart framing members in the wall, roof, or floor framing of a building.

[0097] The fibrous insulation product 100 includes an insulating layer 102 having nonwoven glass fibers and a binder composition for holding the glass fibers together. Optionally, the fibrous insulation product 100 may further include a facing or facing material 104 attached or otherwise attached to the insulating layer 102. The fibrous insulation product 100 has a first side 106, a second side 108 opposite and spaced apart from the first side 106, a third side 110 extending between the first side 106 and the second side 108, and a fourth side 112 opposite and spaced apart from the third side 110 and extending between the first side 106 and the second side 108. The fibrous insulation product 100 further includes a first face 114 connecting the sides 106, 108, 110, 112 to one another and a second face 116 located parallel or generally parallel to and opposite the first face 114 to connect the sides 106, 108, 110, 112 to one another. The fibrous insulation product 100 has a length L1, a width W1, and a thickness T1 in an uncompressed state. In some embodiments, the length L1 is greater than the width W1, and the width W1 is greater than the thickness T1.

[0098] The facing 104 can be placed on the insulation layer 102 to cover all or a portion of the first face 114, the second face 116, or both faces of the fibrous insulation product 100. The facing 104 can take a wide variety of forms. The facing 104 can be a single piece of material or multiple different pieces or sheets of material, and such facings can include a single layer of material or several layers of material. In the illustrated embodiment of FIG. 1, the facing 104 is a single piece of material that covers all of the first face 114 of the fibrous insulation product 100.

[0099] The facing 104 can be constructed from a wide variety of materials. Any material suitable for use in a fiber insulation product can be used. For example, the facing 104 can be constructed from a non-woven fiberglass and polymeric medium, a polymeric medium, a woven fiberglass and polymeric medium, a facing material, such as a polymeric facing film, a scrim, a fabric, a woven fabric, a fiberglass reinforced kraft paper (FRK), a foil-scrim-kraft paper laminate, recycled paper, or calendared paper.

[0100] A significant amount of insulation placed within the building's insulation cavity is in the form of an insulation blanket rolled from an insulation product, such as the insulation products described herein. The faced insulation product is installed with the facing 104 placed flat on the edge of the insulation cavity, typically on the inside of the insulation cavity. In general, insulation products in which the facing is a vapor barrier are commonly used to insulate wall, floor, or ceiling cavities that separate a warm interior space from a cooler exterior space. The vapor barrier is placed on one side of the insulation product to slow or prevent the movement of water vapor through the insulation product.

[0101] FIG. 2 illustrates an exemplary embodiment of an apparatus 118 for manufacturing the fiber insulation product 100. The fiber insulation product 100 may be manufactured in a continuous process by fiberizing molten glass, coating the molten glass fibers with a binder, forming a fiberglass pack on a porous moving conveyor (also called a "forming chain"), and curing the binder to form the insulation blanket, as shown in FIG. 2. The glass may be melted in a tank (not shown) and fed to a fiber forming device, such as one or more fiberizing spinners 119. The spinners 119 are shown as fiber forming devices in the illustrated embodiment, but it will be understood that other types of fiber forming units may be used to form the fiber insulation product 100. The spinners 119 are rotated at high speeds. Centrifugal force forces the molten glass through small orifices in the circumferential sidewall of the fiberizing spinners 119 to form glass fibers. The random length glass fibers 130 may be allowed to fall off of the fiberizing spinner 119 and blown generally downward (ie, generally perpendicular to the plane of the spinner 119 ) by a blower 120 positioned within the forming chamber 125 .

[0102] The blower 120 redirects the glass fibers 130 downwardly. As the glass fibers 130 pass downwardly through the forming chamber 125 and are still hot due to the drawing operation, they are blown by the annular spray ring 135 with the aqueous binder composition, resulting in a relatively uniform distribution of the binder composition throughout the glass fibers 130. Water can also be applied, for example by spraying, to the glass fibers 130 in the forming chamber 125 to at least partially cool the glass fibers 130 prior to application of the binder composition.

[0103] The glass fibers 130, with the uncured aqueous binder composition attached thereto, may be collected and formed into a fiber pack 140 on an endless forming conveyor 145 within the forming chamber 125, assisted by pulling a vacuum (not shown) through the fiber pack 140 from beneath the forming conveyor 145. During the forming operation, residual heat from the air flowing through the glass fibers 130 and fiber pack 140 is generally sufficient to volatilize most of the water from the binder, after which the glass fibers 130 exit the forming chamber 125, leaving the remaining components of the binder composition on the glass fibers 130 as a viscous or semi-viscous high solids liquid.

[0104] The resin coated fiber pack 140, in a compressed state due to the flow of air through the fiber pack 140 in the forming chamber 125, is then transferred from the forming chamber 125 under exit rollers 150 to a transfer zone 155 where the fiber pack 140 expands vertically due to the resilience of the glass fibers 130. The expanded fiber pack 140 is then heated, for example, by conveying the fiber pack 140 into a curing oven 160 where heated air is blown into the fiber pack 140 to evaporate any remaining water in the binder composition, cure the binder composition, and firmly bind the glass fibers 130 together. The curing oven 160 has a perforated upper oven conveyor 165 and a perforated lower oven conveyor 170 that draw the fiber pack 140 between the conveyors 165, 170. The heated air is forced by fan 175 through lower oven conveyor 170, fiber pack 140, and upper oven conveyor 165. The heated air exits curing oven 160 through exhaust 180.

[0105] Additionally, within the curing oven 160, the fiber pack 140 may be compressed by upper and lower perforated oven conveyors 165, 170 to form the insulating layer 102 of the fiber insulation fabric 100. The upper and lower oven conveyors 165, 170 may be used to compress the fiber pack 140 to provide the insulating layer 102 with its predetermined thickness T1. It should be understood that although FIG. 2 shows the conveyors 165, 170 in a substantially parallel orientation, the conveyors may alternatively be positioned at an angle relative to one another (not shown).

[0106] The cured binder composition provides strength and resilience to the insulation layer 102. It should be understood that drying and curing of the binder composition can be performed in either one step or two separate steps. The two-step process is commonly referred to as B-staging. The curing oven 160 may be operated at a temperature between 100° C. and 325° C. or between 250° C. and 300° C. The fiber pack 140 may remain in the curing oven 160 for a period of time sufficient to crosslink (cure) the binder composition and form the insulation layer 102.

[0107] Once the insulation layer 102 exits the curing oven 160, a facing 193 may be placed on the insulation layer 102 to form the facing layer 104. The facing 193 may be attached to the first face 114, the second face 116, or both faces of the insulation layer 102 by a binder (not shown) or some other means (e.g., stitching, mechanical interlocking) to form the fibrous insulation product 100. Suitable binders include adhesives, polymeric resins, asphalt, and bituminous materials that may be coated or otherwise applied to the facing 193. The fibrous insulation product 100 may then be rolled up for storage and / or shipping or cut to length by a cutting device (not shown). It should be understood that in some exemplary embodiments, the insulation layer 102 exiting the curing oven 160 is wound onto a take-up roll or cut into sections of desired length and not surfaced with the facing 193.

[0108] It has surprisingly been discovered that ultra-fine glass fibers with diameters less than 3.81 microns, or 15HT, can be utilized at lower product weights and thicknesses than anticipated to produce fibrous insulation products with desirable thermal properties and material efficiency. Insulation products formed with fibers having an average diameter less than 15HT may hereinafter be referred to interchangeably as "ultra-fine fiber" insulation products or "inventive" fibrous insulation products.

[0109] Without wishing to be bound by theory, the unique combination of very fine fibers with diameters less than 15HT, a low viscosity formaldehyde-free binder composition, and certain processing parameters facilitate the orientation of more fibers (or fiber segments) within a certain range of angles along a plane generally parallel to the forming chain (referred to herein as the L1 direction or machine direction). Thus, the inventive fiber insulation products made from these combinations have a more aligned fiber orientation along the L1 direction than is found in otherwise comparable insulation products made with fibers having an average fiber diameter greater than 15HT. Thus, when the inventive fiber insulation products are installed in a wall cavity, ceiling, floor, or similar building structure, the oriented fibers are aligned in a plane more perpendicular to the direction of heat flow, thereby reducing the product's ability to conduct heat through the thickness of the material.

[0110] 3 is an illustration of an SEM image showing the above-mentioned orientation of fibers (or fiber portions) along a plane generally parallel to the plane of the L1 direction. The SEM image was taken of a microfiber insulation product 200 comprised of glass fibers with an average fiber diameter of 14.5HT, having an R-value of 22, and a formaldehyde-free binder composition including monomeric polyol and polycarboxylic acid crosslinker. The SEM image in FIG. 3 shows a 2.5 mm×1.5 mm product sample with localized fiber vectors (fiber portions in a particular plane).

[0111] 4 and 5 are SEM images further illustrating the fibrous insulation product samples, the product sample in FIG. 4 consisting of glass fibers with an average fiber diameter of 14.5 HT and an R value of 22 (hereafter referred to as Sample A) and the product sample in FIG. 5 consisting of glass fibers with an average fiber diameter of 16.7 HT and an R value of 21 (hereafter referred to as Sample B). The SEM images of Sample A and Sample B were obtained using a Thermo Scientific Prisma SEM and the images were stitched using Thermo Scientific MAPS software. The samples were cut in the machine direction cross section, mounted on SEM stubs using carbon glue and carbon paste, and sputter coated with Au. Fiber orientation was measured and quantified using the Orientation J plug-in from Image J software. The sigma of the Gaussian window was set to 1 pixel and the Gaussian gradient was selected for the structure tensor.

[0112] The surface area (5.24 mm x 3.14 mm) for each of Sample A and Sample B in the machine direction was imaged and analyzed for orientation distribution. To analyze the orientation distribution, localized glass fibers (or fiber vectors or portions thereof) were measured. A plot of orientation frequency (normalized) versus orientation (degrees) was provided for each sample. Figures 6-8 show the weight percentage of fibers (or fiber vectors or portions thereof) in Sample A within ±50°, ±30°, and ±15° of a common plane (0°) parallel to the product length L1.

[0113] Surprisingly, an increased percentage of the glass fibers (or fiber vectors or portions thereof) are oriented along the common plane compared to insulation products having the same R-value but containing glass fibers with an average diameter greater than 15HT. In particular, for any of the exemplary embodiments, at least 30% by weight of the fibers (or fiber vectors or portions thereof) in the microfiber insulation product can be oriented within ±15° of the common plane. FIG. 6 is a graph outlining exemplary fiber orientation distributions within ±15° of the common plane of a fiber insulation product of the present invention formed with glass fibers having an average fiber diameter of 14.5HT. In such embodiments, the microfiber insulation product can include or consist of at least 35%, at least 40%, and at least 44% by weight of such fibers (or fiber vectors or portions thereof) oriented within ±15° of the common plane. For any of the exemplary embodiments, the common plane can be a plane parallel to the length and width of the insulation product.

[0114] It has further been found that for any of the exemplary embodiments, at least 50% or at least 55% by weight of the glass fibers (or fiber vectors or portions thereof) in the fiber insulation product may be oriented within ±30° from the common plane. Figure 7 is a graph outlining an exemplary fiber orientation distribution within ±30° from the common plane of a fiber insulation product of the present invention formed with glass fibers having an average fiber diameter of 14.5HT. In such embodiments, the fiber insulation product may include or consist of at least 57%, at least 60%, at least 65%, and at least 69% by weight of such fibers (or fiber vectors or portions thereof) oriented within ±30° from the common plane. For any of the exemplary embodiments, the common plane may be a plane parallel to the length and width of the insulation product.

[0115] In yet another exemplary embodiment, at least 75% by weight of the fibers (or fiber vectors or portions thereof) in the microfiber insulation product are oriented within ±50° of the common plane. FIG. 8 is a graph outlining an exemplary fiber orientation distribution within ±50° of the common plane of a fibrous insulation product of the present invention formed with glass fibers having an average fiber diameter of 14.5HT. In such an embodiment, the fibrous insulation product can include or consist of at least 78%, at least 80%, at least 82%, and at least 85% by weight of such fibers (or fiber vectors or portions thereof) oriented within ±50° of the common plane. For any of the exemplary embodiments, the common plane can be a plane parallel to the length and width of the insulation product.

[0116] 9(a) is a SEM image showing the fiber orientation of an enlarged sample size area (24 mm×16 mm) of an exemplary microfiber insulation product formed in accordance with the present invention (hereinafter referred to as Sample C). Sample C has an R value of 22 and includes glass fibers having an average fiber diameter of about 14HT and a formaldehyde-free binder composition having a viscosity of about 2,000-3,000 cps at 60%-65% solids, including about 25-30% sorbitol and about 65-70% polyacrylic acid crosslinker by weight. The aqueous binder composition of Sample C has a viscosity of less than 12,000 cps at a solids content of 74.5% and less than 6,000 cps at a solids content of 70% or less.

[0117] The binder composition in the SEM image in FIG. 9(a) was used to measure localized fiber vector orientation (fiber portion viewed at a particular cross section).

[0118] 10(a), in comparison, is an SEM image showing the fiber orientation of a microfiber insulation product having an R-value of 22, also within the scope of the present invention, the microfiber insulation fiber comprising glass fibers having an average fiber diameter of about 14HT and a formaldehyde-free binder composition having a viscosity of less than 2,000 cps at 60%-65% solids, the aqueous binder composition of which is hereinafter referred to as Sample D. The aqueous binder composition of Sample D has a viscosity of less than 12,000 cps at a solids content of 74.5% and a viscosity of less than 6,000 cps at a solids content of 70% or less.

[0119] SEM images of Samples C and D were obtained using a Thermo Scientific Prisma SEM and the images were stitched together using Thermo Scientific MAPS software. Samples were cut in the machine direction cross section, mounted on SEM stubs using carbon glue and carbon paste, and sputter coated with Au. Fiber orientation was measured and quantified using the Orientation J plug-in from Image J software. The sigma of the Gaussian window was set to 1 pixel, and a Gaussian gradient was selected for the structure tensor.

[0120] The surface area (24 mm x 16 mm) for each of Samples C and D in the machine direction was imaged and analyzed for orientation distribution. As with Samples A and B, localized glass fibers (or fiber vectors or portions thereof) from Samples C and D were measured and analyzed to analyze the orientation distribution. Plots of orientation frequency (normalized) versus orientation (degrees) were provided for each sample. Figures 9(b) and 10(b) show the weight percentage of fibers (or fiber vectors or portions thereof) in Samples C and D, respectively, within ±50°, ±30°, and ±15° of a common plane (0°) parallel to the product length L1.

[0121] Surprisingly, it was found that decreasing the binder viscosity used to form Sample D increased the percentage of glass fibers (or fiber vectors or portions thereof) oriented along a common plane. In particular, as shown in FIG. 9(b) and in Table 2 below, 32.94% by weight of the fibers (or fiber vectors or portions thereof) in Sample C were oriented within ±15° from the common plane, 57.07% by weight were oriented within ±30° from the common plane, and 78.87% by weight were oriented within ±50° from the common plane. Further, as shown in FIG. 10(b) and in Table 2 below, 45.14% by weight of the fibers (or fiber vectors or portions thereof) in Sample D were oriented within ±15° from the common plane, 66.23% by weight were oriented within ±30° from the common plane, and 84.03% by weight were oriented within ±50° from the common plane. As discussed above, the common plane may be a plane parallel to the length and width of the insulation product. TIFF2024522502000003.tif40153

[0122] Additionally, while at least a portion of the fibers (or fiber vectors or portions thereof) in the fiber insulation product are oriented along a plane generally parallel to the forming chain or "L1 direction", the fiber insulation product may further include a portion of the fibers (or fiber vectors or portions thereof) oriented along a plane generally perpendicular to the L1 direction. Such "dual orientation" fiber insulation products demonstrate superior thermal performance while exhibiting improved recovery and / or improved compression resistance. Dual orientation fiber insulation products may have at least 10% by weight, at least 15% by weight, at least 18% by weight, at least 20% by weight, at least 25% by weight, at least 28% by weight, and at least 30% by weight of the fibers (or fiber vectors or portions thereof) oriented along a plane generally perpendicular to the L1 direction.

[0123] In some exemplary embodiments, the fibrous insulation product has an increased amount of parallel fiber bundles 202, which include at least two fibers oriented in a substantially parallel direction and bundled together at one or more locations along the length of the fiber. The enlarged SEM images in Figures 11(a)-11(c) show the parallel fiber bundles present in the fibrous insulation product. Figures 12(a)-12(c) further provide enlarged SEM images of the fibrous insulation product shown in Figure 3, further showing the widespread parallel fiber bundles. The parallel fiber bundles 202 can form bonds with single fibers 204 or with other parallel fiber bundles 202.

[0124] For any of the exemplary embodiments, at least 15% by weight of the fibers in the fibrous insulation product 200 may be at least partially contained in parallel fiber bundles. In other exemplary embodiments, at least 20%, at least 25%, at least 28%, at least 30%, at least 35%, at least 40%, at least 45%, and at least 50% by weight of the fibers in the fibrous insulation product may be at least partially contained in parallel fiber bundles.

[0125] Additionally, for any of the exemplary embodiments disclosed herein, the fiber insulation product may have a reduced presence of binder gussets extending between at least two fibers. As defined herein, binder "gusset" means a portion of the cured binder composition that extends between at least two fibers, typically in a triangular or diamond shape, similar to an angle bracket. Binder gussets are measured by microscopy (e.g., optical microscopy or scanning electron microscopy). For optical microscopy, the use of a refractive index solution to "hide" the glass fibers facilitates identification of the binder-fiber bond and gussets. SEM images showing exemplary binder gussets are provided in Figures 13(a) and 13(b).

[0126] Binder gussets occur between non-parallel fibers, meaning that the fibers are oriented in different planes. Without being bound by theory, it is believed that minimizing binder gussets and increasing the presence of binder composition along the length of the fibers is beneficial in both improving uniform orientation and increasing the presence of parallel fiber bundles.

[0127] Due to increased uniformity in fiber orientation, in some exemplary embodiments, 40% or less by weight of the binder composition present in the fibrous insulation product is contained within the binder gussets. For any of the exemplary embodiments, 35% or less by weight of the binder composition is contained within the binder gussets, including 30% or less by weight, 25% or less by weight, 20% or less by weight, 15% or less by weight, 10% or less by weight, and 5% or less by weight.

[0128] Further, due to increased uniformity in fiber orientation, 75% or less by weight of the binder is contained within a binder node, which is a portion of the binder composition distributed at an intersection between two or more intersecting fibers. In some exemplary embodiments, the amount of binder contained within the binder node is limited to 60% or less by weight, including 50% or less by weight, 45% or less by weight, and 40% or less by weight.

[0129] As discussed above, various product and product parameters are believed to affect the orientation of fibers in microfiber insulation products. Without being bound by theory, it is believed that the increased abundance of fibers (or fiber vectors or portions thereof) oriented generally in a plane parallel to the L1 direction is due, at least in part, to the synergistic combination of small diameter glass fibers (i.e., average fiber diameter of 3.81 microns (or 15HT) or less) and the low viscosity formaldehyde-free binder composition. In particular, at a temperature of 25° C., the binder composition has a viscosity of 90,000 cP or less at a solids concentration of 65% to 70% by weight, including viscosities of 50,000 cP or less, 25,000 cP or less, 15,000 cP or less, 10,000 cP or less, and 4,000 cP or less at 25° C. and a solids concentration of 65% to 70% by weight.

[0130] In addition to impacting fiber orientation, the low viscosity of the binder composition allows for a reduction in moisture of the fiber pack on the "ramp" as it moves from the forming chamber into the curing oven. Importantly, the ramp moisture is low enough when the fiber pack enters the curing oven so that the product cures completely and consistently throughout the thickness of the pack. In some exemplary embodiments, the viscosity of the binder composition is adjusted to ensure ramp moisture levels of 7% or less, including levels of 5% or less, 3% or less, and 2% or less.

[0131] The fiber insulation product has a binder content (LOI: loss on ignition) of the fiber insulation product of 10% or less by weight, of the fiber insulation product of 8.0% or less by weight, of the fiber insulation product of 6.0% or less by weight, or of the fiber insulation pack of 3.0% or less by weight. For any of the exemplary embodiments, the insulation product has a binder content (LOI) of the fiber insulation product of 1.0% to 10.0% by weight, including 2.0% to 8.0% by weight, 2.5% to 6.0% by weight, or 3.0% to 5.0% by weight. The relatively small amount of binder contributes to the flexibility of the final insulation product. For any of the exemplary embodiments, the fiber insulation product has an LOI of less than 4.5%, including less than 4.2%, less than 4.0%, less than 3.8%, and less than 3.5%.

[0132] Without being bound by theory, the orientation of small diameter fibers (i.e., fibers having an average fiber diameter of 15HT or less or 3.81 microns or less) in a plane generally more parallel to the L1 (or machine) direction plane has resulted in the formation of fiber insulation products having surprisingly improved thermal performance and overall material efficiency. The thermal performance of fiberglass insulation products is based on the R-value of the fiberglass insulation product, where R-value is a measure of a product's resistance to heat flow. R-value is determined by the following equation (1): Equation (1): R=T1 / k (1) where "T1" is the thickness of the insulation product in inches, "k" is the thermal conductivity of the insulation product in BTU-inches / (hr·ft·°F), and "R" is the R-value of the insulation product in (hr·ft·°F).

[0133] As used herein, the thickness (T1) of the insulation product may be calculated in accordance with ASTM C167-18, and both the k value and areal weight (in pounds per square foot) may be calculated in accordance with ASTM c518-17 or ASTM C177-19.

[0134] The R-value, thermal conductivity, and material efficiency of an insulation product are parameters that provide an indication of the thermal performance of the insulation product.

[0135] Material Efficiency (“ME”) is calculated using the following equation (2): Equation (2): ME=R value / W The insulation efficiency can be calculated by: where “ME” is R·ft2 / lb, where “R” is the R-value of the insulation product and “W” is the areal weight of the insulation product in pounds / ft2. ME measures how efficiently an insulation product resists heat flow and is a metric that can be used to quantify the performance of fiberglass insulation batts. To achieve higher values ​​of R·ft2, insulation suppliers generally increase the amount of insulating material (measured in pounds-mass (ib)). Thus, insulation that provides a higher R·ft2 per pound of material is desirable, as measured by ME (i.e., the insulating effectiveness of the product divided by the amount of material used to provide the insulating effectiveness).

[0136] Thermal Conductivity The microfiber insulation products of the present invention demonstrated a significantly greater reduction in thermal conductivity than expected for a given density. For example, a 1995 publication by Saint Gobain (Langlais, C., Guilbert, G., Banner, D., and Klarsfeld, S., "Influence of the Chemical Composition of Glass on Heat Transfer through Glass Fiber Insulations in Relation to Their Morphology and Temperature," J. Thermal Insulation and Building Envs., Vol. 18, 1995, pp. 350-376) (hereinafter referred to as the "SG publication") details a theoretical approach to predict the thermal performance of fibrous insulations. The SG publication indicates that besides temperature and density, the average diameter of the fibers has been found to be a means for reducing thermal conductivity, and the SG publication provides data showing the effect of fiber diameter on thermal conductivity. Applicants have developed proprietary modeling techniques, independent of the SG publication, that predict curves nearly identical to those shown in the SG publication. Thus, the data provided in the SG publication (hereinafter the "Predicted Results") are deemed to represent the expected thermal performance of fiberglass insulation at various densities and various fiber diameters.

[0137] However, the thermal conductivity values ​​of the fiberglass insulation product of the present invention having an average fiber diameter of 3.6 microns over a density range of 0.2 pcf to 1.6 pcf are unexpectedly lower than the predicted thermal conductivity values ​​based on the predicted results. Figure 14 shows the difference between the predicted results (based on a fiberglass insulation product having an average fiber diameter of 3 microns) and the measured thermal conductivity values ​​of the 3.6 micron fiberglass insulation product of the present invention. As shown, the thermal conductivity values ​​determined by the predicted results are calculated based on the following formula (I): Formula (I) y=0.116x 2 -0.3002x+0.4319 where y is the thermal conductivity (k value) in BTU-in / (hr·ft·F) and x is the product density in pounds per cubic foot (“pcf”). Equation (I) corresponds to R 2 =0.9804, indicating a high degree of accuracy in this formula. In contrast, the measured thermal conductivity values ​​for the 3.6 micron insulation product of the present invention are given by formula (II), i.e., Formula (II) y=0.1013x 2 -0.2438x+0.3763 where y is the thermal conductivity (k value) in BTU-in / (hr·ft·F) and x is the product density in pounds per cubic foot or pcf. 2 = 0.9803, which indicates a high degree of accuracy in this formula.

[0138] Thus, at a given density, the 3.6 micron insulation product of the present invention demonstrated a significantly lower thermal conductivity than would be expected based on an insulation product having a finer fiber average fiber diameter (3.6 microns versus 3.0 microns). For example, at a density of 0.8 pcf, equation (I) outputs a predicted thermal conductivity result of 0.2660 BTU-in / (hr·ft·°F), and the 3.6 micron fiberglass insulation product of the present invention demonstrated a lower measured thermal conductivity (k value) of 0.2461 BTU-in / (hr·ft·°F). The reduction in k value of 0.0199 is a statistically significant reduction.

[0139] In some embodiments, the fibrous insulation products of the present invention demonstrate a reduction in k-values ​​of at least 0.01 BTU-in / (hr·sq ft·°F) compared to expected results across a density range from 0.2 pcf to 1.35 pcf, including reductions in k-values ​​of at least 0.015 BTU-in / (hr·sq ft·°F), at least 0.03 BTU-in / (hr·sq ft·°F), at least 0.05 BTU-in / (hr·sq ft·°F), at least 0.075 BTU-in / (hr·sq ft·°F), at least 0.1 BTU-in / (hr·sq ft·°F), at least 0.15 BTU-in / (hr·sq ft·°F), at least 0.2 BTU-in / (hr·sq ft·°F), and at least 0.23 BTU-in / (hr·sq ft·°F).

[0140] For any of the exemplary embodiments provided herein, the fibrous insulation product has a thermal insulation capacity, expressed in BTU-in / (hr·ft 2 ·°F), that satisfies the following formula (III): Formula (III): y=0.116x 2 -0.3002x+0.4219 where x is the product density in the range of 0.2 pcf to 1.6 pcf. Formula (III) is based on formula (I) but reduced by 0.01 to ensure sufficient separation for expected results. In these or other exemplary embodiments, the fibrous insulation product, expressed in BTU-in / (hr·ft·°F), satisfies the following formula (IV): Formula (IV) y=0.1013x 2 -0.2438x+0.3763 where x is the product density in the range of 0.2 pcf to 1.6 pcf.

[0141] Although certain advantages can be exemplified in insulation products with low density (i.e., less than 1.6 pcf), the density of the fibrous insulation product may vary in various embodiments. The density of the fibrous insulation product as used herein refers to the density of the product after the binder composition is cured and cured, and the product after curing is in a free state (i.e., not compressed or stretched). In various embodiments, the density of the fibrous insulation product ranges from 0.2 pcf to 2.7 pcf. Table 3 lists the original densities (in pcf) for various exemplary embodiments of fibrous insulation products having ultra-fine fibers ranging from 2.03 μm (8.0 HT) to 3.81 μm (15 HT). In Table 3, fiber diameter refers to the average fiber diameter measured by the air flow resistance method described above prior to application of the binder composition. Thickness and original density refer to the thickness and density of the product after the binder composition is cured, and the product after curing is in a free state (i.e., not compressed or stretched). TIFF2024522502000004.tif120153

[0142] The data in Table 3 represents fibrous insulation products with average fiber diameters of 15HT or less, original densities ranging from 0.371 pcf to 1.214 pcf, and R-values ​​ranging from 11 to 49, produced with binder compositions of 6% or less by weight.

[0143] Material Efficiency As mentioned above, material efficiency is a measure of the insulating value of a product (R·sq ft) per pound of insulating material, expressed as R·sq ft / lb. By maximizing material efficiency, an insulation product can provide high insulating performance at the lowest possible weight. In other words, the insulation product of the present invention can achieve the same insulating performance at a lower weight / density because of its high material efficiency. Reducing the product weight reduces the amount of fiberglass and binder material required, thus reducing overall costs (e.g., manufacturing, storage, transportation, and / or disposal costs). In addition, a lower density product is lighter and easier to handle than a higher density product for the same bag area of ​​product.

[0144] Unexpectedly, it has been found that the fibrous insulation products of the present invention demonstrate a surprising increase in material efficiency compared to the material efficiency predicted based on predicted results. With high material efficiency, the fibrous insulation products of the present invention can provide the desired thermal insulation performance (R-value) at a lower areal weight than predicted areal weight.

[0145] 15 illustrates the difference in material efficiency between the predicted results output and the actual material efficiency of a 3.6 micron insulation product of the present invention at a thickness of 5.5 inches, based on a fiberglass insulation product with an average fiber diameter of 3 microns and a thickness of 5.5 inches. As shown in FIG. 15, the predicted material efficiency of the fiber insulation product as determined by the predicted results is given by the following formula (V): Formula (V) y=35.7480145x 2 -112.2450311x+123.2764898 where y is the material efficiency in R·ft2 / lb and x is the product density over a range of densities from about 0.5 pcf to about 1.5 pcf. Equation (V) corresponds to R 2 = 0.9980374, indicating a high degree of accuracy in the model. In contrast, the actual material efficiency of the 3.6 micron insulation product of the present invention is given by equation (VI), i.e., Formula (VI) y=40.1916068x 2 -120.5813540x+131.7360668 where y is the material efficiency in R·ft2 / lb and x is the product density over a range of densities from about 0.7 pcf to about 1.35 pcf. Equation (VI) corresponds to R 2 = 0.9980374, which indicates a high degree of accuracy in this formula.

[0146] At a given density, the 3.6 micron insulation product of the present invention demonstrates a higher material efficiency than would be predicted based on an insulation product having a finer average fiber diameter (3.0 microns versus 3.6 microns). For example, at a density of 0.8 pcf, formula (V) predicts a material efficiency of 56.36 R·sq. ft / lb, while the 3.6 micron fiberglass insulation product of the present invention demonstrates an actual material efficiency of 60.99 R·sq. ft / lb, an increase of more than 4 units. Similarly, at a density of 0.6 pcf, formula (V) predicts a material efficiency of 68.80 R·sq. ft / lb, while the 3.6 micron fiberglass insulation product of the present invention demonstrates an actual material efficiency of 73.86 R·sq. ft / lb, an increase of more than 5 units.

[0147] Thus, the fibrous insulation products of the present invention demonstrate increased material efficiencies of at least 4.0 units, and in some cases at least 5.0 units, at least 5.5 units, at least 5.8 units, and at least 6.0 units compared to expected material efficiencies over the density range from 0.2 pcf to 1.6 pcf.

[0148] For any of the example embodiments provided herein, the fibrous insulation product can have a material efficiency of at least 50, e.g., at least 55, at least 58, at least 60, at least 63, at least 65, at least 68, at least 70, at least 75, and at least 80, according to the formula ME=R-value / area weight (W), for an R-value of 19-24, an areal weight of 0.3 lbs / sq. ft. to 0.5 lbs / sq. ft., and a density of 0.7 pcf to 1.35 pcf.

[0149] Since individual insulation products may contain certain variations within the product itself, it should be understood that the thermal performance values ​​provided above are provided above average expected values ​​that do not take into account this natural variation. Thus, to account for the natural product variation, formula (VI) above may be adjusted by a variation value, which has been calculated as 2.1076693 at the 95% confidence level. Thus, taking into account this variation value, the adjusted material efficiency of the insulation product of the present invention can be calculated using formula (VII), i.e.: Formula (VII) y=40.1916068x 2 -120.5813540x+129.628397 where y is the adjusted material efficiency in R·ft2 / lb and x is the product density over a density range from about 0.5 pcf to about 1.5 pcf.

[0150] FIG. 16 graphically illustrates the material efficiency difference between the predicted result output based on a fiberglass insulation product with an average fiber diameter of 3 microns and a thickness of 5.5 inches and the adjusted material efficiency of a 3.6 micron insulation product of the present invention at a thickness of 5.5 inches and including variation variables.

[0151] As shown in Figure 16, the adjusted material efficiency of the 3.6 micron insulation product of the present invention demonstrates a higher material efficiency than the predicted results based on an insulation product having a finer fiber average fiber diameter (3.6 microns versus 3.0 microns). For example, at a density of 0.8 pcf, formula (V) (predicted results) predicts a material efficiency of 56.36 R·sq ft / lb, while the 3.6 micron fiberglass insulation product of the present invention demonstrates an adjusted material efficiency of 58.89 R·sq ft / lb, an increase of more than 2 units. Similarly, at a density of 0.6 pcf, formula (V) predicts a material efficiency of 68.80 R·sq ft / lb, while the 3.6 micron fiberglass insulation product of the present invention demonstrates an adjusted material efficiency of 71.75 R·sq ft / lb, an increase of more than 3 units.

[0152] Although certain advantages can be illustrated for products having various areal weights, certain advantages may be obtained at relatively low areal weights while maintaining desired thermal properties. As used herein, the areal weight of the fibrous insulation product is the weight per square foot of the insulation product (pounds per square foot) after the binder composition has cured. In various embodiments, the areal weight of the fibrous insulation product is in the range of 0.1 to 2.0 pounds per square foot, including 0.2 pounds per square foot to 1.8 pounds per square foot, 0.25 pounds per square foot to 1.5 pounds per square foot, 0.3 pounds per square foot to 1.2 pounds per square foot, 0.35 pounds per square foot to 1.0 pounds per square foot, and 0.38 pounds per square foot to 0.6 pounds per square foot. For any of the exemplary embodiments, the area weight of the fibrous insulation product can be less than 0.55 pounds per square foot, including less than 0.5 pounds per square foot, less than 0.48 pounds per square foot, less than 0.45 pounds per square foot, and less than 0.42 pounds per square foot.

[0153] In addition, as discussed above, the benefits of improved thermal and material efficiency can be obtained at any insulation product thickness, with certain benefits being obtained at relatively low product thicknesses. In general, to improve the R-value of an insulation product, the thickness (T1) of the insulation product can be increased, which can reduce the density of the product (assuming no other changes are made to the product). However, increasing the product thickness is not possible for a constrained product (i.e., a product installed in a wall cavity of a fixed thickness). Thus, no R-value benefit can be obtained by making the product thicker than the thickness of the wall cavity, since the insulation product can only expand to the thickness of the wall opening. For any of the exemplary embodiments, the thickness T1 of the fibrous insulation product can be about 20 inches or less, including thicknesses of 18 inches or less, 15 inches or less, 12 inches or less, 10 inches or less, 8 inches or less, 7 inches or less, and 6 inches or less. For example, in some thickness constrained products, the fibrous insulation product may have a thickness that is less than 7 inches, including less than 6.5 inches, less than 6 inches, less than 5.5 inches, less than 5 inches, less than 4.5 inches, and less than 4 inches. In these or other embodiments, the fibrous insulation product may have a thickness of, for example, between 0.5 inches and 8 inches, including between 0.75 inches and 7.5 inches, between 0.9 inches and 7.0 inches, between 1.0 inches and 6.8 inches, between 1.5 inches and 6.3 inches, and between 2.0 inches and 6.0 inches.

[0154] Table 4 shows the structural and thermal properties for two exemplary fibrous insulation products (Example 1 and Example 2), where Example 1 and Example 2 are formed with fibers having average fiber diameters of 14.5HT and 14.4HT, respectively. Each of the products of Example 1 and Example 2 was formed with a formaldehyde-free binder composition including a monomeric polyol and a polymeric polycarboxylic acid crosslinker. Example 1 and Example 2 had a thickness of 5.5 inches and an insulation value of R-22. As shown in Table 4 below, at a k value of 0.25 BTU-in / (hr·ft·°F), Example 1 and Example 2 demonstrated low densities of 0.746 lb / ft3 and 0.759 lb / ft3, respectively, with LOI values ​​of less than 4%. In contrast, Comparative Example 1 was formed with 15.9HT glass fiber and a binder composition including a polymeric polyol and a polycarboxylic acid monomeric crosslinker. The product of Comparative Example 1 demonstrated a density of 0.830 lb / ft 3 at a thickness of 5.5 inches and a k value of 0.25 BTU-in / hr·ft 2 ·°F, which is at least 7% higher, specifically at least 9% higher, than the densities of Examples 1 and 2.

[0155] Even more surprisingly, Comparative Example 2 was formed with 14.3HT glass fibers (thereby considered to be "microfibers" as defined herein) and a binder composition including a polymeric polyol and a polycarboxylic acid monomer crosslinker. The product of Comparative Example 2 demonstrated a density of 1.25 lbs / ft3 at a thickness of 5.5 inches and a k value of 0.23 BTU-in / (hr·ft2·°F), which is at least 39% higher than the densities of Examples 1 and 2. TIFF2024522502000005.tif176153

[0156] Furthermore, at the same thickness and nearly the same R-value, Examples 1 and 2 increased material efficiency by over 5 units compared to the products of Comparative Examples 1 and 2. These differences can be attributed at least to the increased areal weight required in Comparative Examples 1 and 2 to achieve k values ​​comparable to those of Examples 1 and 2. Thus, as can be seen, the fibrous insulation products of the present invention can provide improved thermal performance at reduced areal weight, thereby improving the overall efficiency of the product.

[0157] The fiberglass insulation material of the present invention may have any combination or subcombination of the properties and ranges of properties disclosed herein. Although the present invention has been illustrated by the description of its embodiments, it is not the intention of the applicant to limit or in any way restrict the scope of the invention as claimed to such details. Additional advantages and additional modifications will be readily apparent to those skilled in the art. Although the fiber insulation product has been described herein as a flexible batt or blanket, other configurations and other geometries can be used. Furthermore, the fiber insulation product can be used in a variety of ways, and such fiber insulation product is not limited to any particular application. Thus, the present invention in its broader aspects is not limited to the specific details, representative apparatus, and illustrated examples shown and described. Thus, departures from such details or modifications can be made without departing from the spirit and scope of the general inventive concept.

Claims

1. 1. An insulation product comprising: A plurality of glass fibers; a crosslinked formaldehyde-free binder composition at least partially coating the glass fibers; the glass fibers have an average fiber diameter in the range of 8HT (2.03 μm) to 15HT (3.81 μm); the insulation product has a length, a width, and a thickness, the length being greater than each of the width and the thickness; at least 30% by weight of the glass fibers in the insulation product are oriented within ±15° of a common plane defined by the length and width of the insulation product; The insulation product has an uncompressed density of between 0.2 pcf (3.2 kg / m 3 ) and 1.6 pcf (25.6 kg / m 3 ).

2. 10. The insulation product of claim 1, wherein at least 15% by weight of the glass fibers in the insulation product are at least partially bundled in a substantially parallel orientation with at least one other glass fiber in the insulation product.

3. The insulation product of claim 1 or 2, wherein prior to crosslinking, the binder composition has a viscosity of less than 40,000 cP at a solids content of 65% to 70% by weight.

4. 10. The insulation product of claim 1, wherein prior to crosslinking, the formaldehyde-free binder composition comprises at least one monomeric polyol and polycarboxylic acid in a combined amount of at least 45 weight percent, based on the total weight of the binder composition.

5. 10. The insulation product of claim 1, wherein the glass fibers are oriented such that no more than 35% by weight of the binder composition is in the form of gussets.

6. The insulation product of claim 1 , wherein the crosslinked formaldehyde-free binder composition is free of Maillard reactants.

7. 1. An insulation product comprising: a plurality of glass fibers having an average fiber diameter in the range of 8HT (2.03 μm) to 15HT (3.81 μm); a crosslinked formaldehyde-free binder composition at least partially coating the glass fibers; Prior to crosslinking, the binder composition has a viscosity of less than 40,000 cP at a solids content of 65% to 70% by weight, the binder composition comprising at least one monomeric polyol; the insulation product has a length, a width, and a thickness, the length being greater than each of the width and the thickness; at least 55% by weight of the glass fibers are oriented within ±30° of a common plane defined by the length and width of the insulation product; An insulation product, wherein at least 15% by weight of the glass fibers in the insulation product are at least partially bundled in a substantially parallel orientation with at least one other glass fiber in the insulation product.

8. 8. The insulation product of claim 7, wherein the glass fibers are oriented such that up to 35% by weight of the binder composition is in the form of gussets.

9. 8. The insulation product of claim 7, wherein at least 75% by weight of said glass fibers are oriented within ±50 degrees of said common plane.

10. 8. The insulation product of claim 7, wherein prior to crosslinking, the binder composition has a viscosity of less than 20 cP at 10% by weight solids.

11. 1. An insulation product comprising: a plurality of glass fibers having an average fiber diameter of less than 15HT; a crosslinked formaldehyde-free binder composition at least partially coating the glass fibers, the crosslinked formaldehyde-free binder composition being formed from an aqueous binder composition including at least one monomeric polyol; The fibrous insulation product has a binder content (LOI) of less than 4% by weight of the insulation product; At least 15% by weight of the glass fibers in the insulation product are at least partially bundled in a substantially parallel orientation with at least one other glass fiber in the insulation product; The glass fibers are oriented such that up to 35% by weight of the binder composition is present in the form of gussets.

12. 12. The insulation product of claim 11, wherein at least 30% by weight of the glass fibers are oriented within ±15° of a common plane defined by the width and the length of the insulation product.

13. 13. The insulation product of claim 11 or 12, wherein prior to crosslinking, the formaldehyde-free binder composition comprises at least one monomeric polyol and polycarboxylic acid in a combined amount of at least 45 weight percent, based on the total weight of the binder composition.

14. 1. A method of forming an insulation product, the method comprising: fiberizing the molten glass into a plurality of glass fibers; coating the glass fibers with an aqueous formaldehyde-free binder composition; randomly depositing the glass fibers onto a moving conveyor to form an uncured glass fiber blanket; and passing the uncured fiberglass blanket through a curing oven to crosslink the binder composition and form the fibrous insulation product. Upon introduction into the curing oven, the uncured fiberglass blanket has a moisture content of 3% by weight or less; the insulation product has a length, a width, and a thickness, the length being greater than each of the width and the thickness; At least 30% by weight of the glass fibers are oriented within ±15° of a common plane of the insulation article; The method, wherein the insulation product has an uncompressed density of between 0.2 pcf (3.2 kg / m 3 ) and 1.6 pcf (25.6 kg / m 3 ).

15. The method of claim 14, wherein the aqueous formaldehyde-free binder composition has a viscosity of less than 40,000 cP at 65% to 70% by weight solids.